2023
DOI: 10.3389/fenvs.2023.1142071
|View full text |Cite
|
Sign up to set email alerts
|

Plastic waste and microplastic issues in Southeast Asia

Abstract: Plastic pollution on land and in oceans is currently a pressing environmental issue. The accumulation of waste has caused severe, irreversible impacts and consequences on marine life, ecosystems, and the environment due to the lack of good waste collection, treatment, and management systems. Limited resources and infrastructure constantly challenge waste management in Southeast Asia. Therefore, we will examine the current plastic situation and issues in Southeast Asia and gain an understanding of the issues of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Recent research has revealed the alarming presence of microplastics in river ecosystems in Southeast Asia, highlighting widespread contamination by tiny plastic particles ( Babel et al, 2022 ). Ng et al (2023) found plastic waste and microplastics in a variety of environmental compartments, including marine waters, freshwater systems, soils, and sediments across multiple Southeast Asian countries and highlighted that countries with higher population densities along their coastlines, such as Indonesia, the Philippines, and Vietnam, are more likely to pollute the ocean with plastic.…”
Section: Emerging Contaminants In the Southeast Asian Environmentmentioning
confidence: 99%
“…Recent research has revealed the alarming presence of microplastics in river ecosystems in Southeast Asia, highlighting widespread contamination by tiny plastic particles ( Babel et al, 2022 ). Ng et al (2023) found plastic waste and microplastics in a variety of environmental compartments, including marine waters, freshwater systems, soils, and sediments across multiple Southeast Asian countries and highlighted that countries with higher population densities along their coastlines, such as Indonesia, the Philippines, and Vietnam, are more likely to pollute the ocean with plastic.…”
Section: Emerging Contaminants In the Southeast Asian Environmentmentioning
confidence: 99%
“…It was found that plastic waste, constituting 40%, predominates in the coastal regions of countries in SEA (Figure 1). The selection of these nine waste categories based on the identification of waste materials has been consistently documented across various scientific studies in SEA (Ng et al, 2023). These categories have been chosen as a common denominator to ensure a standardized and comprehensive approach to waste characterization and analysis.…”
Section: Coastal Debris Characteristicsmentioning
confidence: 99%
“…The issue of coastal debris, driven by several factors such as improper waste management, lack of public awareness and education, insufficient massive action, and inadequate policy and regulation enforcement, has gained significant attention in recent years (Vince and Hardesty, 2018;Herdiansyah et al, 2021).Over the past decade, this issue has become a focal point for governments, scientists, and various stakeholders (Seltenrich, 2015;Vriend et al, 2021) due to its significant impact on socioeconomic, ecosystem, and environmental factors (Gall and Thompson, 2015;Van Dyck et al, 2016;Faizal et al, 2022). To tackle this environmental challenge, there is an urgent need for comprehensive measures to manage and mitigate debris problems (Ng et al, 2023). Nevertheless, collecting marine debris remains challenging, which leads to it being left stranded on beaches for long periods and having a negative impact on coastal ecosystems (Kong et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, global plastic production reached approximately 390.7 million metric tons, leading to significant consequences for the marine environment [1]. Plastics found in the environment can be categorized into five classes based on their size like nanoplastics (<1 µm), microplastics (≥1 µm to <5 mm), mesoplastics (≥5 mm to 5 cm), macroplastics (>5 to 50 cm), and megaplastics (>50 cm) [2].…”
Section: Introductionmentioning
confidence: 99%